THE FUTURE OF THE PUBLIC ACCOUNTING PROFESSION: AN ANALYSIS OF THE IMPACT OF LAW NUMBER 4 OF 2023 CONCERNING THE DEVELOPMENT AND STRENGTHENING OF THE FINANCIAL SECTOR (P2SK) - Indah Lia Puspita; Indri Syahfitri; Mita Permata Sari; Novita Yolanda (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT The increasing complexity of the financial sector requires a legal system that is capable of adapting to the dynamics of economic activities and the need for more integrated governance. The Government of Indonesia has responded to this need through Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK), which aims to harmonize various financial sector regulations while strengthening the roles of institutions and supporting professions within the sector. One of the professions receiving particular attention in this reform framework is the public accounting profession, which plays a strategic role in ensuring the credibility and reliability of financial statements. This study aims to analyze the regulatory changes introduced by the P2SK Law, identify their impacts on the public accounting profession, and examine their implications for the future development of the profession in Indonesia. The research employs a qualitative approach using a content analysis method to examine the provisions contained in the P2SK Law as well as related regulations that influence the practice of public accounting. The analysis was conducted through several stages, including the identification of key regulatory concepts, mapping of relationships among regulations, comparison with previous regulatory frameworks, and interpretation of policy impacts on the profession. The findings indicate that the P2SK Law strengthens the position of public accountants within the financial services ecosystem through the harmonization of professional definitions, the clarification of the roles of supporting professions, enhanced legal certainty, and the implementation of governance based on the Three Lines Model approach. These reforms also create broader market opportunities for the public accounting profession while encouraging improvements in professional competence and professionalism in response to regulatory changes in the financial sector. ABSTRAK Perkembangan sektor keuangan yang semakin kompleks menuntut sistem hukum yang mampu beradaptasi dengan dinamika aktivitas ekonomi dan kebutuhan tata kelola yang lebih terintegrasi. Pemerintah Indonesia merespons kebutuhan tersebut melalui Undang-Undang Nomor 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Keuangan (P2SK) yang bertujuan menyelaraskan berbagai regulasi sektor keuangan serta memperkuat peran lembaga dan profesi pendukung di dalamnya. Salah satu profesi yang memperoleh perhatian dalam kerangka reformasi ini adalah profesi akuntan publik yang memiliki peran strategis dalam menjamin kredibilitas dan keandalan laporan keuangan. Penelitian ini bertujuan untuk menganalisis perubahan regulasi yang diperkenalkan melalui Undang-Undang P2SK, mengidentifikasi dampaknya terhadap profesi akuntan publik, serta menelaah implikasinya bagi perkembangan profesi tersebut di Indonesia. Penelitian menggunakan pendekatan kualitatif dengan metode content analysis terhadap ketentuan dalam Undang-Undang P2SK serta berbagai regulasi terkait yang memengaruhi praktik profesi akuntan publik. Analisis dilakukan melalui beberapa tahapan, yaitu identifikasi konsep kunci dalam regulasi, pemetaan hubungan antar peraturan, perbandingan dengan regulasi sebelumnya, serta interpretasi dampak kebijakan terhadap profesi. Hasil penelitian menunjukkan bahwa Undang-Undang P2SK memperkuat posisi akuntan publik dalam ekosistem sektor jasa keuangan melalui harmonisasi definisi profesi, penegasan peran profesi penunjang, peningkatan kepastian hukum, serta penerapan pendekatan tata kelola berbasis Three Lines Model. Reformasi ini juga membuka peluang pasar yang lebih luas bagi profesi akuntan publik sekaligus mendorong peningkatan kompetensi dan profesionalisme dalam menghadapi perubahan regulasi di sektor keuangan.